Teaching Deep Culture to Develop Intercultural Communicative Competence (ICC) for EFL Pre-service Teachers - Avifah, Ianatul; Sari, Nur Laily Lupita (Lembaga Riset dan Inovasi Masyarakat Madani, 2024)
In common, EFL (English as a Foreign Language) teachers primarily provide surface-level cultural knowledge to their pupils, who are then expected to use critical thinking to delve into the material. Unfortunately, Universitas Billfath's pre-service teacher education program experienced the same situation. However, candidates for language teachers should possess intercultural competency, which means they should learn about both visible and hidden aspects of culture. To prepare pre-service teachers for their future careers, this study suggests that they be taught profound cultural issues. This will help them to enhance their intercultural communicative competence (ICC). To be specific, this study began with a brief overview of the teaching context and participants. Additionally, a critical analysis of incorporating deep culture to develop ICC was examined. This article also provided an illustration of how the method of teaching deep culture is organized and the reasoning behind it.